Pengaruh Sikap Dan Persepsi Kemudahan Terhadap Keputusan Nasabah Menggunakan Mobile Banking Di Kota Pariaman - Zaki, Zaki (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of Attitudes and Perceptions of Ease of Customer Decisions to Use Mobile Banking in Pariaman City. Taking this title is based on the economic phenomenon that has occurred in recent years, the occurrence of covid-19 is the main factor that customers prefer to use mobile banking in transactions, thereby reducing activities outside the home. This research uses quantitative research. Data taken by distributing questionnaires to customers in Kota Pariaman. With the results of the study stating that the results of the tests that have been carried out have proven that partially the attitude and perceived convenience variables have a significant influence on customer decisions, and simultaneously both variables have a significant influence on customer decisions, and it can also be seen that the Adjusted R Square of 0.774 or of 77.4% This means that 77.4 of the customer decision variables are influenced by attitudes and perceptions of convenience, the remaining 22.6% are influenced by other variables outside of this research variable.